Avaliação das populações de linfócitos produtores de IFN-g e IL-17 em pacientes sépticos e relação com o desfecho clínico - Santos, Michelle Carolina dos [UNIFESP] (2010)
The inflammatory response is modulated during sepsis and up or down regulation of cell activity depends on cells and functions evaluated. IFN-g and IL-17 are cytokines characteristics of lymphocyte subsets Th1 and Th17, respectively, and play an important role in immune response, linking innate and adaptative immunity. Objective: To evaluate the presence of Th1 and Th17 cells in septic patients at admission of the study (D0) compared it with healthy volunteers and after 7 days (D7) follow-up. Material and Methods: We included 59 septic patients on D0, of which 31 had samples collected on D7, and 30 healthy individuals. The peripheral blood mononuclear cells were separated and frozen in liquid nitrogen. After thawing and adjust the concentration to 1x106 cells/mL, cells were stimulated or not with PMA/ionomycin for 30 minutes and maintained at 37oC 5% CO2. Brefeldin A was added and cells were incubated for another 15 hours. Then cells were surface stained for identification of TCD4 lymphocytes (CD3+CD8-). Cells were permeabilized and stained for detection of IL-17A and IFN-g intracellular. The samples were read in FACSCanto cytometer and analyzed with FlowJo program. Results: The basal production of IFN-g and IL-17A was higher in patients compared to healthy volunteers (P=0,002 e P<0,001, respectively). After stimulation, the production of IL-17A was higher in patients (P=0,027) while the IFN-g was higher in healthy (P=0,001). An increase IFN-g production after stimulation with PMA/ionomycin was found in patients with septic shock compared to severe sepsis (P=0,039). The baseline production of IFN-g and after PMA/Ionomycin stimulation was found to be increased in D7 in relation to D0 (P=0,007 e P=0,018, respectively). In contrast, the production of IL-17 after stimulation was higher in D0 compared to D7 (P=0,003). In patients who died, the D0 samples showed lower constitutive IFN-g production compared to D7 (P=0,023), but after a stimulus, no difference was found. In patients who survived, there was no difference at baseline and after stimulation with PMA/ionomycin. The IL-17 production, after stimulation, was higher in D0 sample compared to D7 (P=0,006) in patients who survived. No difference between D0 and D7 was found in patients who survived. Conclusion: The results with higher basal detection of IFN-g and IL-17 producing cells in septic patients reflect the degree of inflammation characteristic of sepsis. A dichotomy between Th1 and Th17 responses after PMA/ionomycin stimulation was found in septic patients, with increased Th17 population and decreased Th1 compared to healthy individuals. A higher proportion of Th1 in D7 was observed in patients who died; while a decrease of Th17 population was observed in patients who survived, indicating that the persistence or higher Th1 and Th17 responses may be deleterious. These findings suggest regulation of the inflammatory response in sepsis of Th1 and Th17 populations.